Praktik Gadai Lahan Dan Dampaknya Terhadap Kesejahteraan Al-Rahin Di Kecamatan Lingsar Kabupaten Lombok Barat - Rois, Ihsan; Huzaini, Moh.; Satarudin, Sataraudin (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2017)
This study aims to determine and analyze the factors that cause a person to pawn the land, how the implementation of mortgage, whether the practice of pawn is in accordance with Islamic law and how the level of welfare al-rahin in District Lingsar West Lombok regency. This study uses qualitative methods, because it examines the reality, phenomena or symptoms that are holistic / intact, complex, dynamic and full of meaning. Data collection techniques are carried out under natural conditions and carried out by means of observation, in-depth interviews and declarations of sound recording and photographs. The informant was set during the field using the snowball sampling technique. The data analysis used is qualitative analysis. The results of the research show that: 1. Most farmers practice land pledge due to financial limitations and partly caused by dishonest dishonesty and to obtain business capital; 2. The practice of pledge in Lingsar subdistrict is more characterized by custom which is a hereditary custom of its predecessors; 3. The practice of pledge of land in Lingsar District is in accordance with the harmonious and pawning conditions according to Islam, but judging from the utilization of collateral goods is not in accordance with the principle of pledge according to Islam, because it gives birth to injustice between al-rahin and al-murtahin; 4. Most of the givers (al-rahin) in Lingsar sub-district have not been prosperous from the perspective of Islam, and the rest have mendapartkan welfare in Islam, because it has fulfilled the needs of dharuriyyat and hajiyatnya